2009
DOI: 10.1152/ajpcell.00048.2009
|View full text |Cite
|
Sign up to set email alerts
|

Negative modulation of inositol 1,4,5-trisphosphate type 1 receptor expression prevents dystrophin-deficient muscle cells death

Abstract: Evidence for a modulatory effect of cyclosporin A (CsA) on calcium signaling and cell survival in dystrophin-deficient cells is presented. Our previous works strongly supported the hypothesis of an overactivation of Ca 2ϩ release via inositol 1,4,5-trisphosphate (IP3) receptors (IP3R) in dystrophindeficient cells, both during membrane depolarization and at rest, through spontaneous Ca 2ϩ release events. Forced expression of minidystrophin in these cells contributed, during stimulation and in resting condition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 50 publications
1
20
0
Order By: Relevance
“…In adult muscles, dystrophin and α-syntrophin regulate PLC activity by stabilizing the sarcolemma; thus, dystrophin absence leads to increased PLC activity (Jordan et al, 2004;Mondin et al, 2009;Sabourin et al, 2012). Furthermore, previous studies showed that dystrophic human samples and murine cell lines expressed high levels of IP3 compared with normal cell lines (Liberona et al, 1998;Mondin et al, 2009) and IP3-induced Ca 2+ release altered gene expression regulation (Powell et al, 2001;Araya et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In adult muscles, dystrophin and α-syntrophin regulate PLC activity by stabilizing the sarcolemma; thus, dystrophin absence leads to increased PLC activity (Jordan et al, 2004;Mondin et al, 2009;Sabourin et al, 2012). Furthermore, previous studies showed that dystrophic human samples and murine cell lines expressed high levels of IP3 compared with normal cell lines (Liberona et al, 1998;Mondin et al, 2009) and IP3-induced Ca 2+ release altered gene expression regulation (Powell et al, 2001;Araya et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In adult muscles, dystrophin and α-syntrophin regulate PLC activity by stabilizing the sarcolemma; thus, dystrophin absence leads to increased PLC activity (Jordan et al, 2004;Mondin et al, 2009;Sabourin et al, 2012). Furthermore, previous studies showed that dystrophic human samples and murine cell lines expressed high levels of IP3 compared with normal cell lines (Liberona et al, 1998;Mondin et al, 2009) and IP3-induced Ca 2+ release altered gene expression regulation (Powell et al, 2001;Araya et al, 2003). In addition, it was determined that modifications in the metabolism of IP3 were fundamental at different stages of muscle development (Carrasco et al, 1997), and others suggested a role for IP3/IP3R during skeletal myocyte development (Rosemblit et al, 1999) and in cardiomyocyte hypertrophy (Arantes et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies showed that the pathological consequence of altered Ca 2ϩ signals observed in the dystrophic skeletal muscle fibers was associated with abnormal IP 3 R distribution (36,37). Knockdown of IP 3 R1 could minimize cell death in dystrophin-deficient muscle fibers (38). Our previous studies showed that Ca 2ϩ spark in the dystrophic (mdx) muscle fibers was irreversible and no longer peripherally confined (4).…”
Section: Discussionmentioning
confidence: 99%
“…In a seminal study performed in cerebellar granules, Carafoli and co-workers (33) found that expression of IP 3 R1 was induced after membrane depolarization with potassium, whereas RyR2 levels remained unchanged. The induction of IP 3 R1 was absolutely dependent on Ca also in skeletal muscle (34), although the mechanism is still unresolved because no NFAT-binding sites have been identified in the IP 3 R1 promoter (35), suggesting that the IP 3 R1 gene might be an indirect target of activity-dependent gene transcription through the calcineurin/NFAT pathway.…”
Section: Regulation Of Receptors For Ip 3 and Ryanodinementioning
confidence: 99%